IMPLEMENTASI PERATURAN DAERAH NOMOR 12 TAHUN 2011 TENTANG RENCANA TATA RUANG DAN TATA WILAYAH KABUPATEN BEKASI TAHUN 2011-2031 - Hidayatulloh, Rizki; Ramdani, Rachmat; Febriantin, Kariena (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The implementation of Bekasi Regency Regional Regulation Number 12 of 2011 concerning the Spatial and Regional Planning for 2011–2031 faces fundamental challenges, particularly regarding the weak control over the conversion of agricultural land into industrial and residential areas. This condition reflects a gap between the spatial planning that has been formally designed and the realities of its execution in the field. In addition, cross-sectoral coordination has not been optimal, monitoring and supervision remain limited, and community participation in maintaining the sustainability of sustainable food agricultural land (LP2B) is relatively low. This study aims to analyze the implementation of Bekasi Regency Regional Regulation Number 12 of 2011 concerning the Spatial and Regional Planning for the period 2011–2031, with particular focus on the protection of Sustainable Food Agricultural Land (LP2B). Employing a qualitative approach with a case study method, this research adopts the Adaptive Implementation Theory, encompassing four key dimensions: flexibility, interaction and communication, monitoring and evaluation, and community participation. The findings reveal that policy implementation is hindered by structural and cultural barriers, including weak intersectoral coordination, limited public participation, and inadequate oversight of spatial violations. The novelty of this research lies in the application of adaptive implementation theory within the regional spatial planning context and its contribution to formulating strategies for institutional capacity-building and improved policy enforcement. This study highlights the urgency of integrating spatial planning with agricultural land protection to ensure sustainable regional development.